2000
DOI: 10.1149/1.1393934
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Doping and Sharp Profiles in Silicon and Silicon-Germanium Epitaxy by Rapid Thermal Chemical Vapor Deposition

Abstract: Background-We conducted a prospective, multicenter, randomized comparison of implantable cardioverter-defibrillator (ICD) versus antiarrhythmic drug therapy in survivors of cardiac arrest secondary to documented ventricular arrhythmias. Methods and Results-From 1987, eligible patients were randomized to an ICD, amiodarone, propafenone, or metoprolol (ICD versus antiarrhythmic agents randomization ratio 1:3). Assignment to propafenone was discontinued in March 1992, after an interim analysis conducted in 58 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 46 publications
6
21
0
Order By: Relevance
“…However, a decrease in the growth rate is observed when the doping ratio is higher than 750 ppm and the smallest growth rate of 26.5 nm/min is obtained when the doping ratio is 7500 ppm. Similar results have been obtained during insitu doping of Ge or Si with P [5,11], where it has been demonstrated that P atoms impedes Ge or Si adsorption by blocking the free active sites on the growth surface and thus leading to the decrease of growth rate. A similar mechanism may also account for the present result on insitu doping of SiGe films.…”
Section: Resultssupporting
confidence: 82%
“…However, a decrease in the growth rate is observed when the doping ratio is higher than 750 ppm and the smallest growth rate of 26.5 nm/min is obtained when the doping ratio is 7500 ppm. Similar results have been obtained during insitu doping of Ge or Si with P [5,11], where it has been demonstrated that P atoms impedes Ge or Si adsorption by blocking the free active sites on the growth surface and thus leading to the decrease of growth rate. A similar mechanism may also account for the present result on insitu doping of SiGe films.…”
Section: Resultssupporting
confidence: 82%
“…This saturation at a rather low value is most probably due to the well-documented tendency of phosphorus atoms of segregating onto the growing surface (see Ref. [38] and references therein), and also to a parasitic gas phase reaction (2PH 3 2P 2 +3H 2 ) at high PH 3 partial pressures that partially inhibits mono-atomic P incorporation into silicon [39].…”
Section: The Boron and Phosphorus Doping Of Simentioning
confidence: 99%
“…[3], strong segregation of P and As in the Si cap layer is shown. In order to control the autodoping, which is unintentional doping due to outgas from reactor wall and/or susceptor, a surface treatment by oxidation and etching or chemical mechanical polishing after P doping and before deposition of an non-doped cap layer are reported [6,7]. It is also reported that lowering the growth temperature of the cap helps to reduce the P segregation [8].…”
Section: Introductionmentioning
confidence: 99%